Analysis Problems of Document Accreditation in Department of Mechanical Engineering, XYZ University - Pradityatama, Maharsa; Kurnia, Fikrihadi; Wijana, Made; Suartika, I Made; Suteja; Fatihah, Hilda (Journal of Industrial Engineering and Innovation, 2024)
Evaluating feasibility and quality of university or department carried out by independent organizations or external agency is accreditation. External quality evaluation is an assessment related to accountability, granting of license by certain agency. Accreditation is an effort to assess and rank Study Programs based on prearranged quality standard. The result of accreditation Study Program ranking is disseminated to public. This research result to analyze problems of preparing accreditation documents in the Mechanical Engineering Department. Accreditation document storage is still not disciplined and integrated, Mechanical Engineering Department lecturers/quality assurance units have not optimized the use of digital archive storage for accreditation purposes. This causes documents that are difficult to find or lost. In addressing this problem, current technological developments can be an alternative solution. File scanning technology that produces digital documents from physical documents which are then uploaded to digital-based storage is expected to be the answer for how to store documents safely and further facilitate the search for these documents. This method can be adopted for optimizing the storage of accreditation documents in Mechanical Engineering Department, Faculty of Engineering, XYZ University